Penerapan Pembelajaran Berdiferensiasi Melalui Model Problem Based Learning untuk Meningkatkan Hasil Belajar IPA di SMP Negeri 2 Mranggen - Murni Tuk Nugroho (Perkumpulan Kualitama Edukatika Indonesia, 2022)
Students' difficulties with science subjects are followed by low student creativity in the learning process. Low student creativity causes low mastery of concepts and ultimately results in low student learning outcomes. Based on the science learning results for class VII.A of SMP Negeri 2 Mranggen for the Final Assessment of Semester 1 for the 2022/2023 Academic Year in class VII.A, the average was 65, while the percentage of learning completion in the 2022/2023 Academic Year, Semester 1 was 70%. To overcome the above problems, it is necessary to develop learning models that can meet student needs. In this research, researchers apply Differentiated Learning through the Problem Based Learning Model. The research was carried out in 2 cycles, each cycle consisting of two meetings. At the second meeting of each cycle, an end-of-cycle review is carried out. The aim of this research is to increase student creativity and learning outcomes on the interaction of living things and their environment. After the end of the action, it is hoped that the average student's classical creativity will reach the Very High criteria, classical learning completeness is expected to reach 85% with the class average score reaching 75. The results of the research show that the application of Differentiated Learning can increase student creativity and learning outcomes as indicated by an increase in the average classical creativity score, the average score of test results and the classical completeness of test results. In cycle 1 the average student creativity score was 76, reaching the High criteria, while in cycle 2 the average creativity score was 88, reaching the Very High criteria. The average value of the test results for cycle 1 = 67 and cycle 2 = 78. Completeness of classical learning results for cycle 1 = 80% and cycle 2 = 87%.